2017
DOI: 10.18632/oncotarget.16207
|View full text |Cite
|
Sign up to set email alerts
|

KSHV co-infection down-regulates HPV16 E6 and E7 from cervical cancer cells

Abstract: High-risk human papillomavirus (HPV) infection is the etiological agent of some malignancies such as cervical, oral and oropharyngeal cancers. Kaposi sarcoma-associated herpesvirus (KSHV) represents a principal causative agent of several human cancers arising in those immunocompromised patients. Interestingly, KSHV DNA has been detected in the oral cavity and the female genital tract, although its detection rate in cervical samples is very low and few reports are about KSHV/HPV co-infection. Therefore, it rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…In our study, the prevalence of HHV-8 in HPV positive cervical lesions was detected in 24.65%, our results join an Iranian study which detected the HHV-8 genome in 22.9% [32 However, a Chinese study showed that the frequency of HHV-8 was similar in the HPV-positive and HPV-negative groups (9.4% vs. 8.0%) [33] Therefore, based on all these studies, we can hypothesize that HHV8 may play a role in uterine cancer progression by causing chronic in ammation. It has been shown that HHV-8 co-infection in SiHa cell lines may increase expression levels of several in ammatory factors including interleukin 6 (IL-6), chemokine (CXC motif) ligand 1 (CXCL1), chemokine (CXC motif) ligand 1 (CXCL1), chemokine (CXC motif) CC ) ligand 5 (CCL5), interleukin 8 (IL-8), macrophage migration inhibitory factor (MIF) ) and plasminogen activator inhibitor 1 (PAI-1) [34,35], With regard to Statistical analyses, a signi cant difference was found respectively with age groups (P = 0.033). And the histological type (P = 0.026) which agrees with the statistical analyzes of another similar study which found a signi cant result with age (P = 0.015), while no signi cance was found for other parameters.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the prevalence of HHV-8 in HPV positive cervical lesions was detected in 24.65%, our results join an Iranian study which detected the HHV-8 genome in 22.9% [32 However, a Chinese study showed that the frequency of HHV-8 was similar in the HPV-positive and HPV-negative groups (9.4% vs. 8.0%) [33] Therefore, based on all these studies, we can hypothesize that HHV8 may play a role in uterine cancer progression by causing chronic in ammation. It has been shown that HHV-8 co-infection in SiHa cell lines may increase expression levels of several in ammatory factors including interleukin 6 (IL-6), chemokine (CXC motif) ligand 1 (CXCL1), chemokine (CXC motif) ligand 1 (CXCL1), chemokine (CXC motif) CC ) ligand 5 (CCL5), interleukin 8 (IL-8), macrophage migration inhibitory factor (MIF) ) and plasminogen activator inhibitor 1 (PAI-1) [34,35], With regard to Statistical analyses, a signi cant difference was found respectively with age groups (P = 0.033). And the histological type (P = 0.026) which agrees with the statistical analyzes of another similar study which found a signi cant result with age (P = 0.015), while no signi cance was found for other parameters.…”
Section: Resultsmentioning
confidence: 99%
“…HHV-8 infection synergistically with HPV can contribute to cervical carcinogenesis through several mechanisms. It is shown that HHV-8 coinfection in SiHa cell line could be promoted the increased expression levels of several inflammatory factors, including interleukin 6 (IL-6), chemokine (C-X-C motif) ligand 1 (CXCL1), chemokine (C–C motif) ligand 5 (CCL5), interleukin 8 (IL-8), macrophage migration inhibitory factor (MIF), and plasminogen activator inhibitor-1 (PAI-1) [ 29 , 30 ]. Indeed, IL-6 has been shown to stimulate cervical tumor growth through vascular endothelial growth factor (VEGF)-dependent angiogenesis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that there was no detectable KSHV DNA in the cervical secretion of 112 females, although 2.7% and 24% respectively of serum samples from the same group were found to contain latent and lytic KSHV antibodies [15].It's now almost unclear whether HPV oncogenic gene expression in cervical cancer cells is regulated by KSHV infection or by KSHV-encoded proteins. [12][13][14][15][16].The major viral oncoproteins closely related to cervical human carcinogenesis are high-risk HPV, as encoded E6 and E7 proteins, for example, under the subtypes 16 and 18 [1,2]. Proteins E6 and E7 can bind to the family proteins P53 and Rb resulting in the control and conversion of the cell cycle [3], respectively.E6 and E7 proteins have been recently shown to be interacting, regulating or contributing to the oncogenesis, and many more cellular elements, including proteins that control cell epigenetic traces and splicing modifications [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, KSHV Co-infection of cervical cancer cells Downregulation of E6 and E7 expression. Although they were identified from cervical cancer cell lines or models of xenograft [12,16], they still stay mainly ambiguous. In spite of hijacking these HPV-encoded major oncogenic proteins expression, KSHV co-infection can maintain cervical cancer cells malignant behaviours, such as invasion, colony formation and tumorigenesis in animal models, which are through the manipulation of some certain cellular genes functions such as MIF and its signaling [16].…”
Section: Discussionmentioning
confidence: 99%